Combined action of anticonvective and thermocapillary mechanisms of instability - Nepomnyashchy, A. A.; Simanovskii, I. B. (Physics of fluids (1994), 2002)
The combined action of the anticonvective and thermocapillary mechanisms of instabilities in two-layer systems has been considered. The systems are subject to an external heating from above and interfacial heat release. Two analytically solvable cases, the case of a model system with the infinitely large heat diffusivity of the bottom fluid and the infinitely small heat expansion coefficient of the top fluid, and the case of long-wave instability in the system between heat insulated horizontal boundaries, have been studied. The convective flows in the real system silicon oil-10 cs-ethylene glycol have been studied by means of the linear stability theory and nonlinear simulations.